Illinois Waterfowl Surveys and Investigations W-43-R-69 Annual Report 1 July 2021 - 30 June 2022 - Fournier, Auriel M.V.; Bradshaw, T.; Gilbert, Andrew D.; Kross, Chelsea A.; Osborn, Joshua M.; Askren, Ryan J.; Beach, Cheyenne R.; Cremer, Chad; Pietrunti, Nicole; Ward, Michael P. (2022)
Illinois Department of Natural Resources Contract no. F21AF01601-00